Peningkatan Hasil Belajar Berhitung Melalui APEI (Aplikasi Edukatif Interaktif) Pada Siswa Tunagrahita Sedang Kelas VI C1 di SLB Negeri Surakarta - Anisa Dian Novita Siregar; Nur Laily Irmawati; Dewi Sri Rejeki (Universitas Sebelas Maret, 2025)
This research was motivated by the low learning outcomes of students with moderate mental disabilities in Mathematics subjects in number elements, especially counting material. Students consisting of 3 students have different abilities. Students A were found not to know the order of numbers correctly. Meanwhile, R students do not yet know the number of numbers or the concept of quantity, while Ri students do not yet know numbers, so learning media are needed that are able to accommodate the learning needs of all students, namely in the form of educational and interactive learning media. The aim of this research is to find out whether the use of Interactive Educational Application (APEI) media is able to improve numeracy learning outcomes in moderately mentally retarded students. The research method used is Class Action Research which is carried out in 2 cycles, namely cycle I and cycle II. Class Action Research is research carried out by teachers in their own class through the self-reflection stage with the aim of improving the learning that has been carried out so that students learning achievements increase. Based on the results of research that has been conducted, the results were obtained that by using APEI students' learning outcomes increased. This can be proven by the percentage score obtained by student R in cycle I a percentage score of 40% is obtained in cycle II a percentage score of 60% is obtained. Meanwhile, students A in cycle I received a score of 30% in cycle II a percentage score of 70% was obtained. Ri learners in cycle I scored 20% in cycle II scored 40%.